The Role of Sharia Financial Literacy, and Word of Mouth by Employees on the Interest of Gold Installment Financing Customers of Bank Syariah Indonesia - Putri Firda Febrianti; Lilis Suaibah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The expansion of Islamic banking in Indonesia has catalyzed diverse financing innovations, including gold installment products offered by Bank Syariah Indonesia (BSI). However, customer adoption remains heterogeneous, necessitating examination of determinant factors. This study investigates how Islamic financial literacy and employee word of mouth (WOM) shape customer interest in gold installment financing through the lens of Theory of Planned Behavior and Information Asymmetry Theory. Employing a qualitative phenomenological approach, in-depth interviews were conducted with ten informants—five customers representing diverse literacy levels and five BSI employees from KCP Sidoarjo Ahmad Yani. Thematic analysis revealed that highly literate customers engage in critical contract evaluation, while those with limited understanding rely predominantly on employee guidance. Employee WOM functions as an educational bridge through storytelling, simulation techniques, and personalized communication. The interaction between literacy and WOM creates synergistic effects: optimal adoption emerges when high literacy combines with effective employee communication. This research contributes a dual-process framework explaining heterogeneous decision pathways in Islamic finance adoption and underscores the strategic integration of financial education with interpersonal communication in enhancing product penetration.